2021
DOI: 10.55446/ije.2021.10
|View full text |Cite
|
Sign up to set email alerts
|

Population Dynamics of Mustard Aphid <i>Lipaphis erysimi</i> (Kaltenbach) and its Natural Enemies

Abstract: A field experiment on the population dynamics of mustard aphid Lipaphis erysimi (Kaltenbach) and its natural enemies in Indian mustard Brassica juncea was conducted during 2016-17 and 2017-18. The peak infestation was observed in the 5th week of January (213.68 aphids/ 10 cm terminal shoot) and 4th week of January (168.80 aphids/10 cm terminal shoot) in the 2016-17 and 2017-18, respectively. The maximum temperature had significant negative effect (r = -0.64), while relative humidity exhibited a significant pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 4 publications
0
0
0
Order By: Relevance
“…Only two genotypes CNH-13-2 and RSPN-29 showed the aphid infestation (Table 5). These results are similar with Srivastava et al, 1995, Prasad, 2003and Ali et al, 2011. By the results of the present study, identification of resistant as well as tolerant varieties to mustard aphid can be done by screening the rapeseed-mustard and can be used for the future endeavors.…”
Section: Resultssupporting
confidence: 90%
“…Only two genotypes CNH-13-2 and RSPN-29 showed the aphid infestation (Table 5). These results are similar with Srivastava et al, 1995, Prasad, 2003and Ali et al, 2011. By the results of the present study, identification of resistant as well as tolerant varieties to mustard aphid can be done by screening the rapeseed-mustard and can be used for the future endeavors.…”
Section: Resultssupporting
confidence: 90%
“…Jandial and Kumar [22] reported that non-significant correlation existed between maximum and minimum temperature, relative humidity and aphid population. Triphati et al [23], Varmora et al [10] Pardhan et al [18] Amarchand et al [20], Dotasara et al [24] were found that the population of ladybird beetle and syrphid fly had a significant positive correlation with aphid population and these findings are full support with present findings.…”
Section: Fig 2 Population Dynamics Of Major Insect Pests Of Cauliflow...supporting
confidence: 87%
“…Patra et al [11], Dwivedi et al [14] and Amarchand et al [20] reported that the C. septempunctata and syrphid fly population was maximum in the third and second week of December. Bana et al [21], Mishra et al [15] and Sharma et al [26] reported that the C. septempunctata population was maximum in the third and fourth week of January.The work of studies on correlation of predators population with the weather parameters are supported by the findings of Arvind [19] Amarchand et al [20] and Dotasara et al [24] reported that the non significant correlation with all weather parameters.…”
Section: Natural Enemiesmentioning
confidence: 72%